A program for detecting geometric cherries based on the analysis of their images - Vereshchaga, Y. V.; Zasipko, V. P. (ТДАТУ, 2021)
The implemented program makes it possible to speed up the process of determining the geometric characteristics of sweet cherry fruits, in comparison with the manual calculation method, and to increase the accuracy of the final result.
Keywords: Computer vision technology; global digital computer technologies